2015
DOI: 10.1073/pnas.1504926112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid replication initiator interactions with origin 13-mers and polymerase subunits contribute to strand-specific replisome assembly

Abstract: Although the molecular basis for replisome activity has been extensively investigated, it is not clear what the exact mechanism for de novo assembly of the replication complex at the replication origin is, or how the directionality of replication is determined. Here, using the plasmid RK2 replicon, we analyze the protein interactions required for Escherichia coli polymerase III (Pol III) holoenzyme association at the replication origin. Our investigations revealed that in E. coli, replisome formation at the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…Then, the δ subunit of clamp loader opens the β-clamp and clamp loader positions it onto primer-template junction, as it is thought to occur during replisome assembly at E. coli oriC . This model is consistent with the results of the in vitro DNA replication experiments performed with the use of ssDNA, containing sequence of RK2 plasmid oriV (Wawrzycka et al, 2015 ). It was demonstrated that TrfA interacts with specific strand of ssDNA of DUE, i.e., the bottom strand, which serves as the site for replisome assembly (Wegrzyn et al, 2014 ; Wawrzycka et al, 2015 ).…”
Section: Replisome Assemblysupporting
confidence: 90%
See 2 more Smart Citations
“…Then, the δ subunit of clamp loader opens the β-clamp and clamp loader positions it onto primer-template junction, as it is thought to occur during replisome assembly at E. coli oriC . This model is consistent with the results of the in vitro DNA replication experiments performed with the use of ssDNA, containing sequence of RK2 plasmid oriV (Wawrzycka et al, 2015 ). It was demonstrated that TrfA interacts with specific strand of ssDNA of DUE, i.e., the bottom strand, which serves as the site for replisome assembly (Wegrzyn et al, 2014 ; Wawrzycka et al, 2015 ).…”
Section: Replisome Assemblysupporting
confidence: 90%
“…This model is consistent with the results of the in vitro DNA replication experiments performed with the use of ssDNA, containing sequence of RK2 plasmid oriV (Wawrzycka et al, 2015 ). It was demonstrated that TrfA interacts with specific strand of ssDNA of DUE, i.e., the bottom strand, which serves as the site for replisome assembly (Wegrzyn et al, 2014 ; Wawrzycka et al, 2015 ). It can be further speculated that TrfA may assist the clamp loader in recognition of the 3′ end of primer-template junction within the oriV .…”
Section: Replisome Assemblysupporting
confidence: 90%
See 1 more Smart Citation
“…Binding of Lon WT, LonK371E/K376E/R379E, and LonR306E/K308E/K310E/K311E to TrfA was analyzed by ELISA as described previously (66) with the following modifications. 200 nM TrfA and 1% (w/v) BSA solution (negative control) were immobilized on the 96-well ELISA plate (Costar) for 90 min.…”
Section: Elisamentioning
confidence: 99%
“…During initiation of replication, the initiator proteins of iteron‐containing plasmids like those of the IncP‐1 group need to interact with host proteins such as DnaA, DnaB, sliding clamp and protein chaperones (DnaKJ/GrpE, ClpB, ClpX, ClpA) (Konieczny et al ., ; Konieczny and Helinski, ; Wickner et al ., ; Wickner et al ., ; Lu et al ., ; Konieczny and Liberek, ; Zhong et al ., ; Kongsuwan et al ., ; Wawrzycka et al ., ). The mutations that occurred in the trfA1 gene during evolution of pMS0506 in S. oneidensis were concentrated in the region coding for the predicted second helix within the TrfA1 N‐terminus region (Hughes et al ., ).…”
Section: Introductionmentioning
confidence: 97%